2008
DOI: 10.1176/appi.ajp.2007.07060879
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Risk of Congenital Cardiovascular Defects Associated With Use of Paroxetine During Pregnancy

Abstract: Paroxetine does not appear to be associated with an increased risk of cardiovascular defects following use in early pregnancy, as the incidence in more than 3,000 infants was well within the population incidence of approximately 1%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(68 citation statements)
references
References 22 publications
1
64
1
2
Order By: Relevance
“…4 In 2005, based on early results of two epidemiologic studies, the US Food and Drug Administration (FDA) warned healthcare professionals that early prenatal exposure to paroxetine may increase the risk of congenital cardiac malformations and reclassified it to pregnancy category D. 5 Most malformations in the early reports leading to the FDA warning were septal defects. Since then, several studies have evaluated the teratogenicity of SSRIs and other antidepressants [6][7][8][9][10][11][12][13][14][15][16][17][18][19] , but considerable controversy remains as to whether this is a "serious concern or much ado about little" as noted in an editorial published with two of the reports. 13,1420 Existing studies have reported different associations, often in the context of multiple comparisons.…”
Section: Conclusion-resultsmentioning
confidence: 99%
“…4 In 2005, based on early results of two epidemiologic studies, the US Food and Drug Administration (FDA) warned healthcare professionals that early prenatal exposure to paroxetine may increase the risk of congenital cardiac malformations and reclassified it to pregnancy category D. 5 Most malformations in the early reports leading to the FDA warning were septal defects. Since then, several studies have evaluated the teratogenicity of SSRIs and other antidepressants [6][7][8][9][10][11][12][13][14][15][16][17][18][19] , but considerable controversy remains as to whether this is a "serious concern or much ado about little" as noted in an editorial published with two of the reports. 13,1420 Existing studies have reported different associations, often in the context of multiple comparisons.…”
Section: Conclusion-resultsmentioning
confidence: 99%
“…This finding led the US Food and Drug Administration to advise women to avoid paroxetine during pregnancy if possible and to change pregnancy labeling from a category C to D. Paroxetine is the only SSRI whose pregnancy category labeling has changed. However, a recent meta-analysis 23 that reviewed both previously published and unpublished data noted no association between paroxetine and cardiovascular defects.…”
Section: Discussionmentioning
confidence: 99%
“…63 Previous research suggested that the inclusion of common reversible Grigoriadis et al heart defects such as the ventral ones may inflate any existing association found with antidepressant exposure. 13,49,52,63 We attempted to differentiate between atrial septal defects and ventral septal defects, but there were not enough studies. Although our ventral septal defects analysis was not significant, the RRs were in a similar range to the overall septal defects analysis, which was significant.…”
Section: Discussionmentioning
confidence: 99%